2022
DOI: 10.1021/jacs.2c03959
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Porous Organic Cages and Covalent Organic Frameworks with Efficient Iodine Vapor Capture Performance

Abstract: The reaction of 5,5′-([2,2′-bipyridine]-5,5′-diyl)diisophthalaldehyde (BPDDP) with cyclohexanediamine and [benzidine (BZ)/[2,2′-bipyridine]-5,5′-diamine (BPDA)], respectively, affords a nitrogen-rich porous organic cage BPPOC and two two-dimensional (2D) covalent organic frameworks (COFs), USTB-1 and USTB-2 (USTB = University of Science and Technology Beijing), under suitable conditions. Interestingly, BPPOC with a single-crystal X-ray diffraction structure is able to successfully transform into USTB-1 and UST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
112
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(125 citation statements)
references
References 95 publications
12
112
0
1
Order By: Relevance
“…Currently, the capture of iodine with solid adsorbents has been demonstrated to be a feasible method for commercial application compared to wet scrubbing of iodine-containing off-gas streams using alkaline solutions. 9 A variety of porous adsorbents, including activated carbon, 10−13 zeolites, 14−17 aerogels, 18,19 covalent organic frameworks (COFs), 3,20,21 metal−organic frameworks (MOFs), 22−25 etc., with intrinsic properties of their porous structure, high specific surface area, and uniformly dispersed functional groups showed exceptional advantages in capturing radioactive iodine. 26−28 Originating from the diverse structural units and modifiable functional groups of organic polymer materials, it exhibits a strong affinity between iodine and the active site of sorbents through Lewis acid−base interactions and superior physicochemical stability.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the capture of iodine with solid adsorbents has been demonstrated to be a feasible method for commercial application compared to wet scrubbing of iodine-containing off-gas streams using alkaline solutions. 9 A variety of porous adsorbents, including activated carbon, 10−13 zeolites, 14−17 aerogels, 18,19 covalent organic frameworks (COFs), 3,20,21 metal−organic frameworks (MOFs), 22−25 etc., with intrinsic properties of their porous structure, high specific surface area, and uniformly dispersed functional groups showed exceptional advantages in capturing radioactive iodine. 26−28 Originating from the diverse structural units and modifiable functional groups of organic polymer materials, it exhibits a strong affinity between iodine and the active site of sorbents through Lewis acid−base interactions and superior physicochemical stability.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Currently, the capture of iodine with solid adsorbents has been demonstrated to be a feasible method for commercial application compared to wet scrubbing of iodine-containing off-gas streams using alkaline solutions . A variety of porous adsorbents, including activated carbon, zeolites, aerogels, , covalent organic frameworks (COFs), ,, metal–organic frameworks (MOFs), etc., with intrinsic properties of their porous structure, high specific surface area, and uniformly dispersed functional groups showed exceptional advantages in capturing radioactive iodine. Originating from the diverse structural units and modifiable functional groups of organic polymer materials, it exhibits a strong affinity between iodine and the active site of sorbents through Lewis acid–base interactions and superior physicochemical stability. However, their complicated preparation process and high cost limit their large-scale applications. Activated carbon is widely used as an iodine adsorbent in the nuclear industry due to its high degree of porosity, but its application is limited on account of weaknesses such as low autoignition temperature, aging problems, and lack of selectivity between water and iodine molecules. , Zeolite molecular sieves are a class of aluminosilicate crystal material with a microporous structure, which is extensively used in the field of gas separation due to its large specific surface area, uniform pore size distribution, excellent thermal stability, and hydrothermal stability .…”
Section: Introductionmentioning
confidence: 99%
“…The high-resolution I3d spectra of 5-Ag 2 O@MCM-41-I along with their fitting results are presented in Figure 6 c. The I3d5/2 peak of 5-Ag 2 O@MCM-41-I were deconvoluted into two components occurring at 619.7 eV and 620.3 eV. The signal at 619.7eV was attributed to I − in AgI [ 42 ], while the peak at 620.3 eV could be ascribed to I 2 [ 43 ], which was formed due to the partial oxidation of iodide by the dissolved oxygen. Li et al and Mao et al have, respectively, reported that iodide could be partially oxidized by dissolved oxygen, forming I 2 [ 42 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The numerous C−H⋅⋅⋅I and C−O⋅⋅⋅I interactions are probably in part responsible for this surprising guest exchange in a water‐saturated crystal. While iodine capture usually requires energy‐intensive material activation, [68–70, 88, 98] PHGC‐1 could be advantageous due to (i) the absence of energy devoted to its synthesis, (ii) its moisture insensitivity, (iii) its absence of energy‐intensive activation step, (iv) the adsorption possible at room temperature and (v) the I 2 /H 2 O selectivity. The dynamics of water motion inside the crystals was probed by DOSY NMR as a function of water replacement by iodine molecules.…”
Section: Discussionmentioning
confidence: 99%
“…All techniques converged toward a � 30 % weight of iodide absorbed which is comparable to the capacity of some zeolites. [88] Iodine uptake capacities of POC based on macrocycles alone clearly exceed the performances of PHGC-1, [68][69][70] but adsorption capacities are recorded at 75 °C and these materials are activated prior to measurements. Beside high recording temperature, it is important to note that material activation is an energy-intensive step, usually followed by unwanted water uptake (for most porous materials) [71,89] thereby limiting their capacity in real conditions, and so restricting their use.…”
Section: Methodsmentioning
confidence: 99%